PERANAN POHON TERHADAP TINGKAT KENYAMANAN LINGKUNGAN KAMPUS UNIVERSITAS LANCANG KUNING PEKANBARU - Hadinoto, hadinoto; Suhesti, Eni; Suwarno, Eno (Fakultas Kehutanan Universitas Lancang Kuning, 2020)
Regional development has a tendency to minimize green open space and also remove the face of nature. The increasingly disharmonious relationship between humans and nature has resulted in ecological deterioration in the environment. Less land covered by trees causes the environment to become hot. The Lancang Kuning University Campus is one of the places of education in which the entire academic community, employees and other parties are located. In carrying out all campus activities, a comfortable environment is needed. The objectives are: to identify tree characteristics in the faculty environment; measuring the comfort level of the faculty environment. The objects this research are tree types. The equipment used is: thermohigro, camera, phi band, haga meter, roll meter, stationery. While the material used is thally sheet. Primary data taken in the field are tree data, temperature and humidity. The comfort index is categorized: comfortable, if it has a value of 21 THI 24; quite comfortable 24 THI 26 and not comfortable THI 26. There were 31 tree species with 472 trunks with an average diameter of 19 centimeters and an average height of 10 meters. The Temperature Humidity Index (THI) of all faculties is in the uncomfortable category.